Biodegradable polymer modified rGO/PANI/CCTO nanocomposites: Structural and dielectric properties. (2018) - Mohammed, J.; Abubakar, B.F; Yerima, K.U.; Hamisu, H.; Isma'il, U.T.; Muhammad, A.; Zulfatu, U.F.; Abubakar, A.; Salihu, N.M.; Abubakar, Mubarak S.; Saidu, Y.; Tekou Carol, T. Tchouank; et al.
Abstract: Nanocomposite of reduced graphene oxide (rGO) stabilised by biodegradable polymer (chitosan), polyaniline and sol-gel derived calcium copper titanate (CCTO) with chemical composition Ca1-x Cex Cu3 Ti4-y Niy O12 (x=0.0, 0.25, 0.45, and y=0.0, 0.3, 0.5) was synthesized. The role of the chitosan is to ensure that the RGO sheets do not restack into graphite. The characteristics D and G bands of graphene oxide (GO) at 1595 and 1353 cm -1 indicate the formation of GO. Dielectric constant and dielectric loss were calculated from the impedance analyser data. The dielectric properties were explained on the basis of Maxwell-Wagner relaxation model and Koop's phenomenological theory. The rGO/PANI/CaCu3 Ti4 O12 nanocomposite shows the highest dielectric constant (7244).